The Shimmering Shining. Issue 1 (1st May 2013) - Freeman, Timothy
Abstract: In response to Hegel's thesis concerning the "end of art, " John Sallis suggests that the future or the "promise of art" may be opened in thinking through Heidegger's essay "The Origin of the Work of Art." Sallis proposes that this promise of art may lie in the capacity to "set forth various elements through transfigurement into shining." In this paper I reflect on what this suggestion concerning the promise of art may mean. Furthermore, I propose that "The Origin of the Work of Art" shows a resonance with Nietzsche's Birth of Tragedy that Heidegger's reading of Nietzsche obscures, and that this resonance is suggested in Sallis' earlier work on Nietzsche's book. I suggest that the Gestalt configuration of "world" and "earth" in Heidegger's essay echoes the configuration of the Apollonian and Dionysian in Nietzsche's thought. I further suggest in the conclusion that this resonance enables one to draw the connection between "The Origin of the Work of Art" and Heidegger's later work in which the promise of art opens up a different mode of dwelling upon the earth.